2008
DOI: 10.1007/s00066-008-1841-3
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesestimulierende Substanzen: günstiges Sicherheitsprofil bei indikationskonformer Anwendung

Abstract: When used as indicated, ESAs are valuable and safe drugs for the treatment of anemia and do not negatively affect patient survival. In particular, the data situation confirms the importance and correctness of the EORTC guidelines 2006 and their recently updated version. It is therefore recommended that these guidelines continue to be strictly followed in the treatment of chemotherapy-induced anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 151 publications
(153 reference statements)
0
21
0
Order By: Relevance
“…Only increases up to the currently recommended target Hb levels result in improvements in tumor oxygenation, and thus may improve prognosis. ESAs should be used as indicated and within the current European Organization for Research and Treatment of Cancer guidelines to achieve the optimum Hb levels [37]. …”
Section: Resultsmentioning
confidence: 99%
“…Only increases up to the currently recommended target Hb levels result in improvements in tumor oxygenation, and thus may improve prognosis. ESAs should be used as indicated and within the current European Organization for Research and Treatment of Cancer guidelines to achieve the optimum Hb levels [37]. …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Adding to this concern are certain clinical trials that reported an association with recombinant human Epo (rHuEpo) treatment and possible tumor progression in patients with head and neck, breast, cervical, and ovarian cancers. 4,5 Many of the reports of high levels of EpoR were based on the detection of EpoR mRNA by nonquantitative reverse transcriptasepolymerase chain reaction (RT-PCR) methodologies or by Western blot analysis and/or immunohistochemical (IHC) staining with anti-EpoR antibodies. Conclusions that EpoR was functionally expressed in tumor cell lines were based on EpoR knockdown, 6,7 signaling, 6,8,9 or proliferation studies.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of active EpoR in tumor tissues might promote cancer growth and thus have a negative clinical outcome in patients (14,15). This hypothesis is underlined by clinical trials demonstrating worse survival rates in rhuEpo-treated lung cancer patients than in control patients (16,17), depending on the treatment schedule (18). Further studies were initiated to elucidate the link between rhuEpo treatment and cancer growth but have not provided clear evidence so far.…”
mentioning
confidence: 99%